Korean ‘Housewives’ and ‘Hipsters’ Are Not Driving a New Illicit Plant Trade: Complicating Consumer Motivations Behind an Emergent Wildlife Trade in Dudleya farinosa - Margulies, Jared D. (Frontiers in Ecology and Evolution, 2020)
Illegal trade in wild plants receives less scientific and policy attention than illegal trade in wild animals and animal-derived products. One exception to this generalizable trend is the recent emergence of an illegal trade in the California succulent species Dudleya farinosa. US officials and mainstream media reporting on these incidents suggest the final destination of these plants is succulent consumer markets in South Korea and other East Asian countries. It is believed that this illegal trade emerged in response to sudden and widespread consumer demand for succulents due to: 1) the increasing popularity of succulent plants in mainstream South Korean and East Asian cultures writ large; and 2) the preferential valuing of ‘wild’ versus cultivated plants by succulent consumers. Based on findings from content analysis of media reports and in-depth qualitative interviews in California and South Korea, I argue instead for a more nuanced perspective of the drivers of this emergent trade, with the primary motivational desire for these plants coming from a selective and highly skilled community of succulent enthusiasts, rather than mainstream plant consumer groups. In presenting these findings I demonstrate the importance of in-depth, critical qualitative research for exploring the emergence of particular trades in wildlife in order to inform more sustainable and legal trades. I clarify the primary drivers of this new trade in Dudleya farinosa as an illegal but logical response to the economics and temporalities of plant trade. I offer suggestions on how these findings can inform more sustainable solutions to the illicit extraction of wild plants in meeting consumer demand.